HPLC separation and isolation of asiaticoside from Centella asiatica and its biotransformation by A. niger - Alfarra, Helmi Yousif; Omar, Muhammad Nor (Engineering and Technology Publishing, 2014)
The study was carried out to develop a rapid and accurate HPLC method to isolate the major bioactive phytochemical asiaticoside in Centella asiatica and to transform this metabolite using microorganism. Asiaticoside was separated using an optimized HPLC method using Phenomenex, Luna, 5 μm (C18) (150 mm x 4.6 mm) eluted with Water PH3: Acetonitrile (50:50 V/V). The reported method is easy, fast and accurate, and produced highly pure, resolved isolate with high concentration. Asiaticoside was biologically transformed by Aspergillus niger, and the prescreening results on TLC and 1D and 2D IR showed that the transformed produced has at least two byproducts of the ancestor compound. In addition to that the preliminary screeing showed that the transformed product showed very high cytotoxicity agains HaCat Cells in comprison to the original compound.